PENGARUH PELATIHAN DAN PEMBERIAN INSENTIF TERHADAP PRESTASI KERJA KARYAWAN PADA PT. SARI MURNI PRATAMA MEDAN - Syaputra, Arry (Universitas Harapan Medan, 2024)
Training provided usually by sending potential employees and have achievements above average to follow the training as managerial training, production processes adapted to the latest ISO, as well as the training is usually level supervisors, managers, the division as well as employees who have the potential to be able to replace one of the available positions. In addition to training, the provision of incentives is one of the efforts made by the company to tie up a skilled workforce in order not to switch to other places. A wage incentive or award given by the company to its workforce on labor efforts that have been forfeited to the company. Incentives are also a motivational tool that can give rise to a boost / stimulation to make employees work harder and passionate and in accordance with what is desired by the company. If the employee worked diligently and passionately, it will be seen from a high performance. The purpose of this study was to determine the effect of training and incentives on employee performance in PT. Murni Pratama Sari Medan. The method used is multiple linear regression. The results showed that by the F test, shows that training and the provision of incentives simultaneously positive and significant impact on employee performance at PT. Murni Pratama Sari Medan. Based on t test results, showing that training and the provision of incentives and significant positive effect on employee performance at PT. Murni Pratama Sari Medan. Based on t test, the incentive is the most dominant factor in this study.